Pengaruh Penghasilan Wajib Pajak, Penerapan E-System dan Pemahaman Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Rury Indah Sintia; Herawati Khotmi; Rusli Amrul (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to determine the effect of taxpayer income, application of e-systems and understanding of tax regulations on individual taxpayer compliance (Kpp Pratama West Mataram study). This study consists of 3 independent variables, namely Taxpayer Income (X1), E-System Application (X2), and Understanding of Taxpayer Regulations (X3) and the dependent variable is Taxpayer Compliance (Y). The population of this research is taxpayers who are registered at KPP Pratama Mataram Barat Mataram office with a total of 35,375 individual taxpayers. Samples were taken using incidental sampling technique. The total sample taken is 100 respondents. The analysis in this study was carried out using multiple linear regression analysis with the help of the SPSS version 22 program. The results of this study indicate that taxpayer income has a significant effect on individual taxpayer compliance at the West Mataram Private Tax Service Office. The implementation of the taxation e-System has no significant effect on taxpayer compliance. Understanding of tax regulations has a significant effect on taxpayer compliance.